Clinical and genetic factors are associated with kidney complications in African children with sickle cell anaemia. (20th September 2021) - Adebayo, Oyindamola Christiana; Betukumesu, DieuMerci Kabasele; Nkoy, Agathe Bikupe; Adesoji, Oluyomi Modupe; Ekulu, Pepe Mfutu; Van den Heuvel, Lambertus P.; Levtchenko, Elena N.; Labarque, Veerle
Summary: Clinical and genetic factors have been reported as influencing the development of sickle cell nephropathy (SCN). However, such data remain limited in the paediatric population. In this cross‐sectional study, we enrolled 361 sickle cell disease children from the Democratic Republic of Congo. Participants were genotyped for the beta (β)‐globin gene, apolipoprotein L1 ( APOL1 ) risk variants, and haem oxygenase‐1 ( HMOX1 ) GT‐dinucleotide repeats. As markers of kidney damage, albuminuria, hyperfiltration and decreased estimated glomerular filtration with creatinine (eGFRcr) were measured. An association of independent clinical and genetic factors with these markers of kidney damage were assessed via regression analysis. Genetic sequencing confirmed sickle cell anaemia in 326 participants. Albuminuria, hyperfiltration and decreased eGFRcr were present in 65 (20%), 52 (16%) and 18 (5·5%) patients, respectively. Regression analysis revealed frequent blood transfusions, indirect bilirubin and male gender as clinical predictors of SCN. APOL1 high‐risk genotype (G1/G1, G2/G2 and G1/G2) was significantly associated with albuminuria ( P  = 0·04) and hyperfiltration ( P  = 0·001). HMOX1 GT‐dinucleotide long repeats were significantly associated with lower eGFRcr. The study revealed a high burden of kidney damage among Congolese children and provided evidence of the possible role of APOL1 and HMOX1 in making children more susceptible to kidney complications.